Estimation of Unrecorded Alcohol Consumption in Low‐, Middle‐, and High‐Income Economies for 2010. (15th April 2016) - Rehm, Jürgen; Larsen, Elisabeth; Lewis‐Laietmark, Candace; Gheorghe, Paul; Poznyak, Vladimir; Rekve, Dag; Fleischmann, Alexandra
Abstract : Background: Consumption of unrecorded alcohol is prevalent, especially in low‐income countries (LIC). Monitoring and reduction of unrecorded consumption have been asked for in the World Health Organization (WHO) global strategy to reduce the harmful use of alcohol. To date, only a few countries have installed monitoring systems, however. Methods: As part of the WHO global monitoring, an expert survey using the nominal group technique, a variant of Delphi studies, was conducted to assess level and characteristics of unrecorded consumption in 46 member states. One hundred experts responded. Descriptive statistics and repeated analysis of covariance were used to analyze the data. Results: The study showed feasibility of the chosen methodology to elicit information of unrecorded consumption with experts responding for 74% of the countries. Response rate was lower for LIC. Compared to prior WHO estimates, experts tended to estimate higher unrecorded consumption for LIC, and lower unrecorded consumption for high‐income countries. Unrecorded consumption was seen as a financial, public health, and social problem by the majority of experts. Homemade alcohol was the most prevalent subcategory of unrecorded consumption globally. Conclusions: The chosen methodology was feasible, and new information about consumption of unrecorded consumption could be gathered. There is still a need for increasing efforts of national monitoring, especially in LIC. Abstract : Consumption of unrecorded alcohol is common, but there has been relatively little systematic monitoring. As a newly established part of the WHO global monitoring, a Delphi expert was conducted to assess level and characteristics of unrecorded consumption in 46 member states. One hundred experts responded. Main results included a systematic gradient of the proportion of unrecorded alcohol of total consumption by wealth of a country, with unrecorded alcohol being relatively most important in low‐income countries (see Figure).